SISTEM PENGAWASAN LEMBAGA PERADILAN DI INDONESIA - Ilmiati Ilmiati (Fakultas Syariah Institut Agama Islam Negeri Palu, 2017)
The type of supervision that will be discussed in this paper is thesupervision conducted by the judiciary. Indonesia has two judicialinstitutions that carry out judicial functions. First, namely theConstitutional Court, performs a supervisory function on theperformance of the government apparatus in the form of judicialreview of the law against the constitution; Secondly, namely theSupreme Court, performs a supervisory function on the performance ofthe government apparatus in the form of judicial product testing whichis hierarchically under the law against the law. In addition, theSupreme Court with a state administrative court structurally under ithas the authority to exercise control over decisions or beschikkingissued by the state apparatus.